Lewy body pathology is more prevalent in older individuals with mitochondrial disease than controls - Daniel Erskine (3471959) (2019)
Mitochondrial diseases arise due to defects in mitochondrial DNA (mtDNA) or nuclear mitochondrial genes (nDNA), leading to impaired mitochondrial oxidative phosphorylation and dysfunction of organs with particularly high energy requirements. Primary mitochondrial diseases affect 1 in 4300 individuals in the UK, making them amongst the most common heritable neurological conditions [2]. Mitochondrial dysfunction has also been linked to deposition of several sporadic age-associated pathologies, including neurofibrillary tangles of hyperphosphorylated tau protein [3] and Lewy body (LB) pathology consisting of aggregated α-synuclein [4], pathological features of Alzheimer’s disease (AD) and Parkinson’s disease (PD)/dementia with Lewy bodies (DLB), respectively. Therefore, we sought to determine whether older individuals with mitochondrial diseases were at increased risk of developing age-associated neurodegenerative pathologies using post-mortem brain samples collected prospectively at Newcastle Brain Tissue Resource (NBTR). Other Information Published in: Acta Neuropathologica License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00401-019-02105-w